Expresia ta este : 1+3+5+7+...+2013-2-4-6-...-2014=1+2+3+4+5+...+2013-(2+4+5+6+...+2012)-2(1+2+3+..+1007) = 1+2+3+4+...+2013-2(1+2+..+1006)-2(1+2+3 +.. +1007) = 2013*2014/2 - 2*1006*1007/2 - 2*1007*1008/2 = 2013*1007 - 1006*1007 - 1007*1008 = 1007*(2013-1006-1008)=1007*(-1)=-1007 Nu am putut sa adaug raspunsul pentru ca nu am mai avut loc ; au facut-o altii care au dat raspunsuri aiurea

Răspunsuri

2014-04-08T23:39:01+03:00
Expresia ta este : 1+3+5+7+...+2013-2-4-6-...-2014=1+2+3+4+5+...+2013-(2+4+5+6+...+2012)-2(1+2+3+..+1007) = 1+2+3+4+...+2013-2(1+2+..+1006)-2(1+2+3 +.. +1007) = 2013*2014/2 - 2*1006*1007/2 - 2*1007*1008/2 = 2013*1007 - 1006*1007 - 1007*1008 = 1007*(2013-1006-1008)=1007*(-1)=-1007